Effect of a Psychological Skills Education Program (PSEP) on Free Kicks and Penalty Kicks For High School soccer player - Dr May Mohammed salman Al tameemi; Dr Sahar Mohammed Salman Al tameemi (مجلة علوم الرياضة, 2020)
Mathematical training science is one of the sciences are concerned with preparing the athlete in a comprehensive manner according to scientific foundations, where indicated (Mayveyev, 167: 1980) the preparation of athletes includes physical and cognitive preparation, skillful preparation, planning preparation, and finally psychological preparation.Players of high athletic levels are close in level and performance, but the decisive factor in this is the psychological factor, which is available to a greater degree among players who have more international participation, and that increases the chances of success and achievement (Vealey & et 1988 )